Anti–JC virus antibody levels in serum or plasma further define risk of natalizumab‐associated progressive multifocal leukoencephalopathy. Issue 6 (24th October 2014) - Plavina, Tatiana; Subramanyam, Meena; Bloomgren, Gary; Richman, Sandra; Pace, Amy; Lee, Sophia; Schlain, Brian; Campagnolo, Denise; Belachew, Shibeshih; Ticho, Barry
<x xml:space="preserve">Abstract</x> Objective The increased risk of progressive multifocal leukoencephalopathy (PML) with natalizumab treatment is associated with the presence of anti–JC virus (JCV) antibodies. We analyzed whether anti‐JCV antibody levels, measured as index, may further define PML risk in seropositive patients. Methods The association between serum or plasma anti‐JCV antibody levels and PML risk was examined in anti‐JCV antibody–positive multiple sclerosis (MS) patients from natalizumab clinical studies and postmarketing sources. For PML and non‐PML patients, the probabilities of having an index below and above a range of anti‐JCV antibody index thresholds were calculated using all available data and applied to the PML risk stratification algorithm. Longitudinal stability of anti‐JCV antibody index was also evaluated. Results Anti‐JCV antibody index data were available for serum/plasma samples collected >6 months prior to PML diagnosis from 71 natalizumab‐treated PML patients and 2, 522 non‐PML anti‐JCV antibody–positive patients. In patients with no prior immunosuppressant use, anti‐JCV antibody index distribution was significantly higher in PML patients than in non‐PML patients (p < 0.0001). Among patients who were anti‐JCV antibody negative at baseline in the AFFIRM and STRATIFY‐1 trials, 97% remained consistently negative or below an index threshold of 1.5 over 18 months. Retrospective analyses of pre‐PML samples collected longitudinally from PML patients displayed sustained higher anti‐JCV antibody index over time. Interpretation Anti‐JCV antibody levels in serum/plasma, measured as index, may differentiate PML risk in anti‐JCV antibody–positive MS patients with no prior immunosuppressant use. Continued evaluation of anti‐JCV antibody index and PML risk is warranted. Ann Neurol 2014;76:802–812